Assessing Socio-Environmental Externalities of Big Hydro Power Projects: The Case of Skavica - Shkurti, Aranit (European Journal of Sustainable Development, 2022)
The transition towards renewable energy sources has increased the interest in Hydro Power generation. The socio-environmental externalities produced from big HPPs have a significant impact on the local communities and on the overall economy of the country. There is consensus in the literature that small HPPs cause fewer and less severe environmental and social externalities than large HPPs. Anyway, the electricity supply is guaranteed by bigger investments and the trade-off is not quite simple to clarify. The study is based on a set of sustainability indicators which provide a life cycle analysis of the Skavica Hydro Power Plant and the relative investment scheme. The aim of this paper is to identify the general externalities related to the construction of a big HPP and to connect to the specific case study of Skavica HPP. Furthermore, the estimation of benefits and costs along with public discussions is integrated to evidence the legitimate social and environmental concerns of people living in areas where dams are planned. Policy options intended to adopt these externalities are also addressed. Keyword: Hydro Power Plant, renewable energy, Skavica, externalities, policy, floodings prevention, electricity